Port2Learn - Siti Shahida, Kamel; Mohamad Faizuan, bin Mat; Maizatul Nurhuda, bt. Saadon; Noorhaslina, binti Senin; Mohamad Zamhari, bin Abolhasan (2018)
Handling between different platforms for teaching and learning can be quite stressful to the educators, especially to those who were not technology-savvy. The main problem faced by today's instructors is having too many teaching & learning platform/system to be handled by one instructor at the same time. As for example, Learning Management System (LMS) is used mainly for teaching & learning contents, material & assessment, while there is another system for students’ attendance, different system for students marks and etc. This will affect the time and efficiency of the educators with the need to cope up with the different platforms. Port2Learn help to curate and organize instructors’s own digital portfolio for teaching and learning, in which all the teaching and learning content and materials, student management system can be linked and gathered in one platform.